Analisis Pemberlakuan Death Penalty Terhadap Pengedar Ilegal Narkotika (Studi Perbandingan Hukum Positif dan Hukum Pidana Islam): Analysis of the Implementation of the Death Penalty for Illegal Narcotics Dealers (A Comparative Study of Positive Law and Islamic Criminal Law) - muhammad iqbal; Abdul Wahab (Universitas Islam Negeri Kiai Haji Achmad Siddiq Jember, 2025)
Drug crime has become a major issue in Indonesia and worldwide. Drug abuse can negatively impact physical health, mental health, emotions, and social life. Drug abuse is an organized crime at the national and international levels. Therefore, this study aims to examine how the death penalty is applied to drug dealers from two perspectives: Positive Law and Islamic Criminal Law, to provide a deeper understanding of the application of the death penalty in drug cases. The main focus of this study is to: 1) What is the death penalty for drug dealers under positive law? 2) What is the death penalty for drug dealers under Islamic criminal law? 3) How does the death penalty for drug dealers compare under positive law and Islamic criminal law in Indonesia? The author uses normative research, analyzing and comparing relevant legal regulations that have been applied in this case to determine whether they contradict each other or whether there is any ambiguity in the norms. The purpose of the comparative methodology in this study is to identify the similarities and differences between the two laws and legal systems.The conclusions of this thesis are: 1) The death penalty for drug dealers in positive law is regulated by Law No. 35 of 2009 concerning Narcotics, and its procedures are regulated by Law No. 2/PNPS/1964. 2) The death penalty in Islamic criminal law does not specify the penalties imposed for drug crimes, and this law makes an analogy between narcotics and alcohol. Therefore, scholars believe the punishment imposed is ta'zir. Furthermore, Islamic criminal law does not specify the procedures or mechanisms imposed on perpetrators of drug crimes. 3) From a positive legal perspective in Indonesia, it is regulated by Law No. 35 of 2009 concerning Narcotics. Some of the sanctions imposed include: Imprisonment and fines for dealers, the death penalty and life imprisonment for dealers who commit repeat offenses, and rehabilitation for drug users. Meanwhile, in Islamic criminal law, drug dealers can be given ta'zir punishment, where the judge has the authority to determine the form of punishment, including flogging. Masalah kejahatan narkotika telah menjadi masalah besar di Indonesia dan di seluruh dunia. Penyalahgunaan obat-obatan terlarang dapat memberikan dampak negatif terhadap pada kesehatan fisik, kesehatan mental, emosi, dan kehidupan bermasyarakat. Penyalahgunaan narkotika merupakan kejahatan yang terorganisir di tingkat nasional dan internasional. Maka dari itu, studi ini bertujuan untuk melihat bagaimana hukuman mati diterapkan pada pengedar narkotika dari dua perspektif: Hukum Positif dan Hukum Pidana Islam, agar dapat memberikan pemahaman yang lebih jauh mengenai penerapan hukuman mati dalam kasus narkotika. Fokus utama dari penelitian ini adalah untuk 1). Bagiamana hukuman mati terhadap pengedar narkotika dalam hukum positif? 2). Bagaimana hukuman mati terhadap pengedar narkotika dalam hukum pidana Islam? 3).Bagaimana perbandingan antara hukuman mati terhadap pengedar narkotika menurut hukum positif dan hukum pidana Islam di Indonesia? Penulis menggunakan penelitian normatif, yaitu menganalisis dan membandingkan aturan-aturan hukum yang berkaitan yang telah diterapkan dalam kasus ini untuk melihat apakah aturan-aturan tersebut bertentangan satu sama lain atau apakah ada kekaburan norma. Tujuan dari metodologi komparatif dalam penelitian ini adalah untuk mengidentifikasi persamaan dan perbedaan antara kedua undang-undang dan sistem hukum tersebut. Kesimpulan dalam skripsi ini adalah 1) Pidana mati terhadap pengedar narkotika dalam hukum positif diatur dalam UU No.35 Tahun 2009 tentang Narkotika dan terkait dengan prosedur nya diatur dalam Undang-Undang Nomor 2/PNPS/1964 2) Pidana mati dalam hukum pidana Islam tidak menjelaskan mengenai hukuman yang menjerat dari tindak pidana narkotika dan dalam hukum ini